The Influence of Green CEO and Family CEO on Water Disclosure in Indonesia - Ivone Ivone; Susanti Susanti; Sukiantono Tang; Santi Yopie (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: Water disclosure in Indonesia has become an important mitigation key for building public trust in anticipatory responses to conflicts related to natural resource scarcity issues. In this case, corporate transparency through water disclosure has become an urgent issue. Therefore, this study aims to analyze the influence of green and family CEO on water resource disclosure related to environmental responsibility. This study was conducted to show transparency and accountability to the public regarding the company's commitment to water disclosure. Research Methodology: Approximately 350 data samples were collected from the Indonesia Stock Exchange (IDX) website after data processing for the period 2021 to 2023. The data were obtained from financial and sustainability reports of various companies and analyzed using descriptive statistical tests, Pearson correlation, and regression analysis. Results: Green CEOs positively influence water resource disclosure, whereas family CEOs have a more dynamic influence. On the one hand, they prioritize data confidentiality, which can limit transparency if considered a threat. However, they are considered a driving force in the disclosure of water-related information. Conclusions: CEO characteristics are a factor in determining crucial water disclosure strategies. Corporate leadership plays an important role in determining transparency. Green CEOs tend to encourage accountability, whereas family CEOs exert a dynamic influence on water disclosure within companies. Limitations: The research period was limited, and the sample was only from Indonesia. Furthermore, the processed data relied on company reports and were subjective, making independent confirmation impossible. Contributions: This study helps in understanding the various characteristics and behaviors of leadership in implementing information-disclosure strategies related to water resources.